A case to think about - Zilberman, Regina (Revista de Letras, 2007)
The premisse that literaly creations is offered to the reader as dialogue, supported by recent theories of reception, is discussed and utilized as the basis for the reading of the short story "The case of the stick" by Machado de Assis.